Animal Protein Consumption Level And The Relationship Of Stunting In Toddlers - Ahmad Suhaimi; Yudhi Harianto; Alfisah (Rawa Sains: Jurnal Sains STIPER Amuntai, 2022)
This study intend to determine the relationship between Animal Protein Consumption Levels with Stunting Incidence in Toddlers in Hantakan District, Hulu Sungai Tengah Regency. This research was carried out in the Hantakan sub-district, Hulu Sungai Tengah district. This type of research is descriptive quantitative research, while the analytical technique used is chi square analysis using the SPSS 20 application. Based on the results of the study from 60 samples, there were 22 children under five in the poor category, 18 under five in the moderate category and 20 in the good category. It can be concluded that the level of animal protein consumption is related to the incidence of stunting in Hantakan District, Hulu Sungai Tengah Regency, because the p-value = 0.001 < 0.005 results Ho is rejected and Ha is accepted.